Social Determinants of Health: A Deep Dive into Nepalese and American Societies - Uprety, Kailash (Rural Development Journal, 2025)
Health inequity is a widespread problem created by unequal social, cultural, and economic environments in society. Based on the "fundamental theory of causes," this paper investigates the role of social context (i.e., socioeconomic status (SES), education, gender, ethnicity, and community environment) as an important causal factor in health inequalities. Through comparisons of two different contexts, Nepal and America, the paper emphasizes the systemic conditions that maintain health inequalities in these societies. Although the problem is presented globally, its dynamics are heterogeneous with regard to regional, cultural, and structural circumstances. The study employed the content analysis to examine and compare secondary data, including scholarly articles, government reports, and demographic surveys. Major publications on the determinants of health inequality and region-specific studies in Nepal formed the base of a comparative analysis. Results demonstrate that in the United States, socioeconomic status, systemic racism, and discrimination in access to healthcare are contributing factors to health disparities. In Nepal, caste/ethnicity, regional differences, and patriarchal systems are important factors of impact. Both countries illustrate the impact of social determinants of health on health outcomes, such as care access, dietary practices, and longevity. The conclusion of the study is that reducing health inequality includes tackling social inequality and providing equitable access to resources.